2020
DOI: 10.1080/1369183x.2020.1804193
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking transit zones: migrant trajectories and transnational networks inTechno-Borderscapes

Abstract: and to the special issue editors Erik Snel, Özge Bilgili, Richard Staring for their thoughtful comments and efforts towards improving our article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…Furthermore, when deciding where to move, meso-level factors may play an important role. For example, migrant networks are considered to be vital for refugees to access information and to receive financial and practical support [57,[66][67][68][69]. Moreover, virtual networks, such as information from social media, are increasingly used by asylum migrants [70].…”
Section: Time-varying Unobservable Factorsmentioning
confidence: 99%
“…Furthermore, when deciding where to move, meso-level factors may play an important role. For example, migrant networks are considered to be vital for refugees to access information and to receive financial and practical support [57,[66][67][68][69]. Moreover, virtual networks, such as information from social media, are increasingly used by asylum migrants [70].…”
Section: Time-varying Unobservable Factorsmentioning
confidence: 99%
“…To date, only a few studies were found that have adopted mobile messaging apps in the context of datagathering strategies among refugees. With an emphasis on the analysis of refugees' daily practices of digital media use, messaging apps have been used by researchers as digital tools to stay in contact with refugee participants and to conduct interviews (Kaufmann, 2018;Marlowe, 2019;Twigt, 2018;Zijlstra & Van Liempt, 2017), as well as part of the ongoing participatory research (Godin & Donà, 2021;Leurs, 2017). A recent study by Palmberger (2022) involved the use of digital diaries among refugees to record their digitally mediated care practices through screenshots from WhatsApp communication with family members.…”
Section: Using Mobile Messaging Apps As a Tool For Data Collectionmentioning
confidence: 99%
“…Their scattered, fractured and global existence may see them encounter 'unexpected obstacles' (Ryan & Mulholland, 2014, p. 152) due to their intense mobility and precarious employment. However, as the respondents note, while dispersed, 'they are always connected', making it clear that scattered networks are not necessarily weak, as the literature on enduring transnational networks state (Godin & Donà, 2021;Vertovec, 2001). Consequently, the real and/or virtual encounters of mobile people are able to create unity, complementarity and flexibility out of their multiplicity and heterogeneity, strengthening existing networks.…”
Section: The Former President Of the League Of Romanian Studentsmentioning
confidence: 99%
“…However, insufficient attention has been paid to the social networks created between migrants linked to their mobility experiences. The concept of migrants’ networks have been analysed in relation to social citizenship (Coward, 2012), highlighting the links between networks, identity and place (Marcu, 2015), social connections (Morosanu, 2013), social capital and livelihood in the context of a community in migration (Ryan et al, 2008; Vertovec, 2001), transnational networks (Godin & Donà, 2021; Vertovec, 2001), virtual online networks (Djundeva & Ellwardt, 2020), highly skilled networking strategies (Ryan & Mulholland, 2014) or student networks (Bouton et al, 2021).…”
Section: Introductionmentioning
confidence: 99%